THE INFLUENCE OF SUPERVISORY WORK MOTIVATION AND COMPETENCE ON THE PERFORMANCE OF SCHOOL SUPERINTENDENTS IN PADANGSIDIMPUAN CITY EDUCATION OFFICE - Khairuddin Tampubolon; Elazhari; Nunti Sibuea (RADJA PUBLIKA, 2023)
The background of this research is related to the performance of school supervisors. School supervisors are ASNs who are one of the school administrative staff assigned to their respective work areas. Permen PAN and RB no. 21 of 2010 article 5 explains that the main duties of school supervisors themselves consist of carrying out academic and managerial supervisory duties in education units. With regard to the main tasks carried out by a school supervisor, of course it is not too much to say that the barometer of national education quality is determined by the level of competence of a school supervisor. Based on the background of the problems above, the problems identified in this study are as follows: 1) The role of school supervisors is not optimal in carrying out supervisory duties and functions, 2) The intensity of attendance of supervisors at target schools is still lacking, 3) Supervisors who come to schools tend to only carry out aspects of managerial supervision while other aspects are given little attention, 4) School supervisors rarely conduct class visits and provide direct guidance to teachers. In addition, school supervisors are considered to be lacking in providing guidance related to educational research. This research uses a quantitative approach. This research was conducted in the Padangsidimpuan City Education Office, on Jl. AH Nasution No. 97 Pijorkoling Padangsidimpuan. carried out from May 2021 to July 2021. with a population of 49 people, data collection techniques were carried out by observing, interviewing and distributing questionnaires/questions. Furthermore, the data were analyzed using SPSS Software Version 26. Based on the results of the study, it was concluded that: 1) The effect of work motivation on supervisory performance is: 67.1%; 2) the influence of Supervisory Competence on Supervisory Performance is: 64.4%; 3) The simultaneous influence of work motivation and competence of supervisors on supervisory performance is 65.6%.